Takotsubo Cardiomyopathy and Sepsis: A Systematic Review. (April 2017) - Cappelletti, Simone; Ciallella, Costantino; Aromatario, Mariarosaria; Ashrafian, Hutan; Harding, Sian; Athanasiou, Thanos
Takotsubo cardiomyopathy (TTC) is characterized by a systolic dysfunction localized in the apical and medial aspect of the left ventricle. It is usually related to physical or emotional stress. Recent evidence highlighting the role of infection led us to analyze the links between TTC and sepsis. A systematic review of the literature was undertaken to assess any trends in clinical findings, diagnosis, and outcomes in such patients. We identified 23 selected papers reporting a total of 26 patients, having sepsis, in whom TTC occurred. For each case, we collected data identifying population characteristics, source of sepsis, clinical disease description, and the results of cardiovascular investigations. The majority of patients were females (n = 16), mean age was 62.8 (14.0 standard deviation) years, and clinical outcome was favorable in 92.3% of the cases once the management of sepsis was initiated. A better understanding of the mechanisms of sepsis-associated TTC may generate novel strategies to treat the complications of this cardiomyopathy and may even help predict and prevent its occurrence.